Instructional Activities and the Quality of Language in Chilean Preschool Classrooms. Issue 3 (3rd April 2018) - Strasser, Katherine; Darricades, Michelle; Mendive, Susana; Barra, Gabriela
ABSTRACT: Research Findings: This study examines the association between preschool classroom activity and the quality of the language spoken by teachers and children. Eighteen classrooms serving low-income children between the ages of 3 and 4 in Santiago de Chile were audio-recorded during one morning shift. Recordings were transcribed and segmented into activities (greeting, learning experience, book sharing, book discussion, breakfast, lunch, free play and other noninstructional time). A total of 113 activity segments were identified. Characteristics of teacher and child language were measured in each segment. Differences between the eight activities were examined using analysis of variance. Activities were classified as instructional or noninstructional, and the association between this dimension and language characteristics was examined using multilevel path analysis. Results show that most of the variance in language outcomes occurs within classrooms. Analyses show that a significant portion of the variance in the way teachers and children talk is explained by the instructional/noninstructional dimension. Instructional activities are characterized by more language stimulation, more teaching, fewer directives, and more child talk than noninstructional activities. Practice or Policy Implications: We discuss implications for teacher professional development and early childhood education improvement in general and for Latin-America specifically.